ANALISIS AMONIAK TERLARUT PADA TANAMAN LAMUN (Thalassia testudinum) DALAM MEDIA AIR - Dewi Sundari; Alimuddin Alimuddin; Rahmat Gunawan (JURNAL KIMIA MULAWARMAN, 2015)
A research about the analysis of dissolved ammonia in seagraas plants (Thalassia testudinum) at water’s media has been carried out. A research aimed to determined the ammonia concentration in the water’s seagrass plants, and also the effect of ammonia variations concentration at the growth water media after planting for 1, 2, 3 dan 4 weeks, and determined the ability of seagrass to absorb dissolved ammonia. Water as its plant media was placed in to 4 cups that have been added dissolved ammonia as 0, 3, 5 dan 7 mg/L respectively. The concentration of dissolved ammonia from water and seagrass samples were measured by phenate method using a visible spectrophotometer at a wavelength of 650 nm. The result showed that during the planting of four weeks the concentration of dissolved ammonia in the water as its plant media decreased while the concentration of dissolved ammonia in seagrass planst increased. The results of the first week, concentration of dissolved ammonia at growth water’s media, respectively for 9,0234 mg/L; 12,5562 mg/L; 14,5293 mg/L and 16,9269 mg/L. After the fourth week, the concentration of dissolved ammonia decreased as 4,0520 mg/L; 7,3479 mg/L; 8,2848 mg/L and 8,4061 mg/L